11-Deoxycorticosterone Producing Adrenal Hyperplasia as a Very Unusual Cause of Endocrine Hypertension: Case Report and Systematic Review of the Literature - Asla, Queralt; Sardà, Helena; Lerma, Enrique; Hanzu, Felicia A.; Rodrigo, María Teresa; Urgell, Eulàlia; Pérez, José Ignacio; Webb, Susan M.; Aulinas, Anna (Frontiers in Endocrinology, 2022)
Background and objectives: 11-deoxycorticosterone overproduction due to an adrenal tumour or hyperplasia is a very rare cause of mineralocorticoid-induced hypertension. The objective is to provide the most relevant clinical features that clinicians dealing with patients presenting with the hallmarks of hypertension due to 11-deoxycorticosterone-producing adrenal lesions should be aware of. Design and methods: We report the case of a patient with an 11-deoxycorticosterone-producing adrenal lesion and provide a systematic review of all published cases (PubMed, Web of Science and EMBASE) between 1965 and 2021. Results: We identified 46 cases (including ours). Most cases (31, 67%) affected women with a mean age of 42.9 ± 15.2 years and presented with high blood pressure and hypokalaemia (average of 2.68 ± 0.62 mmol/L). Median (interquartile range) time from onset of first suggestive symptoms to diagnosis was 24 (55) months. Aldosterone levels were low or in the reference range in 98% of the cases when available. 11-deoxycorticosterone levels were a median of 12.5 (18.9) times above the upper limit of the normal reference range reported in each article and overproduction of more than one hormone was seen in 31 (67%). Carcinoma was the most common histological type (21, 45.7%). Median tumour size was 61.5 (60) mm. Malignant lesions were larger, had higher 11-deoxycorticosterone levels and shorter time of evolution at diagnosis compared to benign lesions. Conclusions: 11-deoxycorticosterone-producing adrenal lesions are very rare, affecting mostly middle-aged women with a primary aldosteronism-like clinical presentation and carcinoma is the most frequent histological diagnosis. Measuring 11-deoxycorticosterone levels, when low aldosterone levels or in the lower limit of the reference range are present in hypertensive patients, is advisable.